VD_FINDINFO Arrêt / 2014 / 899 vom 16. Dezember 2014 - VD Tribunal cantonal (2014)
RENTE D'INVALIDITÉ, RÉVISIONDÉCISION, RECONSIDÉRATION | 28 LAI, 4 LAI, 16 LPGA, 17 al. 1 LPGA, 53 al. 2 LPGA, 7 LPGA, 8 LPGA